Development process of a rubric for assessment of leadership competences in project management scenarios - Souza, Mariane Cásseres (2021)
In the field of Project Management, leadership competences have a significant impact on project execution, and are identified as a key factor in the success of an organization. In this regard, defining strategies and tools for development and assessment of leadership competences is a significant contribution to project management research and practice. Scenario-based learning is an interesting approach for development of a wide range of competences because it involves real problems and allows practitioners to face challenges based on their own professional experience. For the assessment process it is possible to identify indicators related to the competences to each scenario. The success of this process is influenced by the instrument that is being used and rubrics are one of the instruments that may be used for competence assessment. A rubric includes criteria and standards considering a specific scale on which different levels of assessment are established. This paper aims to describe the process of creating and validating a rubric, designed to assess leadership competences in project management scenarios, considering the Individual Competency Baseline (ICB). To illustrate this design and validation process, only one criteria of the rubric will be presented. The design of the rubric includes five phases, and includes internal validation based on an expert agreement, considering content, construct and criteria validation of the rubric. The expected outcomes of this work are the presentation of the results of the internal validation process that was conducted by two experts. As future work, the final version of the rubric will be developed as a contribution to assess leadership competences in project management scenarios.